"The Paradox of Deep Learning: Inequality of Digital Access in the Implementation of Social Sciences Deep Learning in 3T Polewali Mandar Regional Elementary School" - rezkia yusuf; Alimin Alwi; Najamuddin (International Journal of Technology and Education Research, 2026)
The implementation of deep learning in elementary school social studies learning is an important part of the educational transformation in the Independent Curriculum. However, its implementation in 3T areas still faces challenges due to inequality of digital access. This study aims to analyze the obstacles to the implementation of deep learning in social studies learning in elementary schools in the 3T area and identify adaptive strategies that can be carried out in conditions of limited access to technology. The research uses a qualitative approach with a case study design through observation, interview, and documentation techniques. The results of the study show that the limitations of technological infrastructure, low teachers' digital literacy, and lack of training are the main factors that hinder the optimal implementation of deep learning. To overcome these conditions, adaptive strategies are needed such as the use of simple technology, the use of the environment as a contextual learning resource, and strengthening teacher competence through institutional support. These findings show that deep learning can still be implemented meaningfully if adjusted to the real conditions of schools in the 3T area.